Influence of psychological factors on the prognosis of temporomandibular disorders pain - Won Jung; Kyung-Eun Lee; Bong-Jik Suh (Elsevier, 2021)
Background/purpose: The leading symptom of temporomandibular disorders (TMD) is pain, and psychological factors are involved in the persistence of TMD-related pain. Therefore, this study was aimed to analyze the influence of psychological factors on the prognosis of TMD-related pain. Materials and methods: The medical records of 486 patients with TMD-related pain were analyzed. Each patient's psychological profile was assessed using the Symptom Checklist-90-Revised (SCL-90-R). Patients were classified into two groups according to a post-treatment numeric rating scale (NRS). Patients with an NRS score of 0 or 1 at the last visit were classified into group G, and those with an NRS score of 2 or greater were classified into group P. Following this, all patients were re-classified into groups N and R according to pain recurrence. Statistical analysis was performed to evaluate differences in the SCL-90-R T scores between the groups. In addition, multiple logistic regression analysis was used to identify psychological factors that affected treatment outcome. Results: The patients in groups P and R had higher scores in all subscales of the SCL-90-R than groups G and N, respectively. In particular, somatization (SOM) and psychoticism (PSY) scores showed significant differences between the groups in the treatment outcome. Conclusion: A correlation is identified between psychological factors and treatment outcome in patients with TMD-related pain. In particular, patients with elevated SOM and PSY scores are more likely to develop refractory pain, and thus require additional interventions to control this risk.